MiR‐124 Negatively Regulates Osteogenic Differentiation and In vivo Bone Formation of Mesenchymal Stem Cells. Issue 5 (May 2015) - Qadir, Abdul S.; Um, Soyoun; Lee, Heesu; Baek, Kyunghwa; Seo, Byoung Moo; Lee, Gene; Kim, Gwan‐Shik; Woo, Kyung Mi; Ryoo, Hyun‐Mo; Baek, Jeong‐Hwa
ABSTRACT MicroRNAs are novel key regulators of cellular differentiation. Dlx transcription factors play an important role in osteoblast differentiation, and Dlx5 and Dlx2 are known targets of miR‐124. Therefore, in the present study, we investigated the regulatory effects of miR‐124 on the osteogenic differentiation and in vivo bone formation of mesenchymal stem cells (MSCs). During osteogenic induction by BMP2, the expression levels of miR‐124 were inversely correlated with those of osteogenic differentiation marker genes in human and mouse bone marrow‐derived MSCs, MC3T3‐E1 cells and C2C12 cells. The overexpression of a miR‐124 mimic significantly decreased the expression levels of Dlx5, Dlx3, and Dlx2, whereas the silencing of miR‐124 with hairpin inhibitors significantly increased the expression of these Dlx genes. Luciferase reporter assays demonstrated that miR‐124 directly targets the 3′UTRs of Dlx3, Dlx5, and Dlx2. The overexpression of a miR‐124 mimic suppressed the osteogenic marker gene expression levels, alkaline phosphatase activity and matrix mineralization, which were all significantly increased by the overexpression of a miR‐124 inhibitor. When ectopic bone formation was induced by the subcutaneous transplantation of human bone marrow‐derived MSCs in nude mice, MSCs overexpressing a miR‐124 inhibitor significantly enhanced woven bone formation compared with control MSCs. However, MSCs overexpressing a miR‐124 mimic exhibited increased adipocyte differentiation at the expense of ectopic bone formation. These results suggest that miR‐124 is a negative regulator of osteogenic differentiation and in vivo bone formation and that the targeting of Dlx5, Dlx3, and Dlx2 genes partly contributes to this inhibitory effect exerted by miR‐124. J. Cell. Biochem. 116: 730–742, 2015. © 2014 Wiley Periodicals, Inc.